2013
DOI: 10.1371/journal.pone.0083220
|View full text |Cite|
|
Sign up to set email alerts
|

Thyroid Ultrasound Findings in Children from Three Japanese Prefectures: Aomori, Yamanashi and Nagasaki

Abstract: Due to the likelihood of physical and mental health impacts following the unprecedented accident at the Fukushima Dai-ichi Nuclear Power Plant, the Fukushima prefectural government decided to conduct the Fukushima Health Management Survey to assist in the long-term health management of residents. This included thyroid ultrasound examination for all children in Fukushima. For appropriate evaluation of ultrasound screening of the thyroid, it is important to understand its reference data of thyroid findings in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 14 publications
(27 reference statements)
4
57
0
4
Order By: Relevance
“…Factors possibly involved in the differences in the incidence rates among different reports include regional differences in the age distribution or iodine intake, family history, differences in the ultrasonographic devices used, differences in the examiners, etc., although no definitive reason has been identified yet. An intrathyroidal ectopic thymus was detected in 9 individuals (4.2%), and its incidence rate decreased with age, similar to the tendency reported by Hayashida N et al [18]. Regarding the development of the thymus, it is known that the epithelium of the third pharyngeal pouch grows to close the inner medulla, then the bilateral primordia of the thymus fuse with each other on the median plane, forming the thymus.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Factors possibly involved in the differences in the incidence rates among different reports include regional differences in the age distribution or iodine intake, family history, differences in the ultrasonographic devices used, differences in the examiners, etc., although no definitive reason has been identified yet. An intrathyroidal ectopic thymus was detected in 9 individuals (4.2%), and its incidence rate decreased with age, similar to the tendency reported by Hayashida N et al [18]. Regarding the development of the thymus, it is known that the epithelium of the third pharyngeal pouch grows to close the inner medulla, then the bilateral primordia of the thymus fuse with each other on the median plane, forming the thymus.…”
Section: Discussionsupporting
confidence: 83%
“…Concerning comparison of the results in this study with the data reported from other districts, the survey of Fukushima Prefecture inhabitants conducted by the Fukushima Prefectural Government revealed cysts in 102594 individuals (45.5%) among the 225537 individuals surveyed, the cysts measuring ≤ 5 mm in diameter in 102583 of the 102594 individuals (99.99% cases) (data as of August 23, 2013 published on the prefecture's homepage) [10]. According to the report by Hayashida N et al, who published combined data from 3 districts (Hirosaki City Aomori Prefecture, Kofu City Yamanashi Prefecture and Nagasaki City Nagasaki Prefecture), cysts were detected in 2483 (56.9%) of 4365 individuals, the cysts measuring ≤ 5 mm in diameter in 2283 of the individuals (91.9%) [18]. In all of these surveys, the incidence rate of cysts was high and cysts ≤ 5 mm in diameter accounted for the overwhelming majority of the cases, similar to the tendency observed at our facility.…”
Section: Disclosure Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Naukowcy z Japonii ocenili również w badaniu ultrasonograficznym tarczycę w 3 regionach swojego kraju wśród 4365 dzieci w wieku 3-18 lat, stwierdzając w 72 (1,65%) przypadkach guzki tarczycy, 61 (1,4%) wole, a u dwojga dzieci agenezję tarczycy (0,04%) [28].…”
Section: 5751-58unclassified
“…В отноше-нии распространенности узлов у детей по данным ультразвукового исследования (УЗИ) и по данным DOI: 10.14341/ket2015440 50 © "Клиническая и экспериментальная тиреоидология", 2015 ауто псии приводятся цифры от 1-5% у детей до 13% у подростков [13,14], причем в первом проспективном исследовании [13] речь идет в основном о частоте РЩЖ и возможном влиянии на его развитие Чернобыльской катастрофы, а вторая работа датирует-ся 1965 г. и даже реферата мне найти не удалось. Вместе с тем дается ссылка на крупное эпидемиологическое исследование, проведенное в Японии [15], в котором на ультразвуковом аппарате экспертного класса было обследовано 4365 детей в возрасте от 3 до 18 лет и вы-явлено 56,88% кистозных образований в ЩЖ, из них только 4,58% диаметром >5 мм, а также 1,65% солид-ных узлов, из них диаметром >5 мм -1,01%. Кроме того, авторами отмечается очень высокая частота экто-пии тимуса (в среднем среди всех возрастных групп -1,95%) с пиком на возраст от 3 до 9 лет -4,6%!…”
Section: из обсуждения раздела рекомендаций по узловому зобу у детейunclassified